Interdisciplinarity and Multidimensional of Entrepreneurship: Review of The Main Definitions - Anna KOMARNICKA1; Pawel MICKIEWICZ2; Bartosz MICKIEWICZ2 (Communications of International Proceedings, 2020)
Entrepreneurship is an ambiguous concept, and has been described differently over the centuries, both in scientific terms and in practice. There are many definitions, concepts of entrepreneurship in the literature, but there is not a consensus regarding their essence. The article presents a review of selected approaches to entrepreneurship. In addition, the aim of the paper is to seek to answer the question: what is entrepreneurship in practice and what does it do? How is the concept of entrepreneurship defined in the literature? Is it possible to discuss the paradigm of entrepreneurship, considering entrepreneurship as an interdisciplinary science?
Keywords: entrepreneurship; entrepreneurial concepts; multidimensionality; entrepreneurial paradigm